ANALISIS KONDISI TRANSFORMATOR UTAMA PT. PLN (PERSERO) UPK TARAHAN LAMPUNG BERDASARKAN HASIL UJI DGA (DISSOLVED GAS ANALYSIS) - Bagus Ramadhan; Moch. Dhofir; Tri Nurwati (Jurnal Mahasiswa TEUB, 2023)
According to SLD Sumatera data, UIP3BS has three load control sub-systems, namely UPB Southern Sumatera, UPB Central Sumatera, and UPB Northern Sumatera with a total of 202 substations and transformers totaling 402 units / 22.594 MVA. Based on these data, it shows the importance of the role of the transformer so it is very necessary to know the condition of the transformer and take appropriate maintenance action against the transformer is very necessary. Therefore, this study aims to assess the condition of the main transformer transformer in unit 4 at PT PLN (Persero) UPK Tarahan Lampung based on the results of DGA (Dissolved Gas Analysis) testing. DGA testing serves to provide information related to the condition of the transformer so that it can take appropriate maintenance actions. In this study, several processes were carried out, namely by taking data from DGA test results in the form of gas value levels of H2, CH4, CO, CO2, C2H4, C2H6, C2H2 dissolved in main transformer oil in unit 4 at PT PLN(Persero) UPK Tarahan. Then analyze the DGA test results using the TDCG method and the Duval's Triangle method. Based on the results of the analysis using the TDCG and Duval Triangle methods, the condition of the main transformer at unit 4 PT. PLN(Persero) UPK Tarahan Lampung in normal conditions. This is also supported by the TDCG value which is well below 720 ppm. Therefore, this condition is still within the permissible limits for the main transformer unit 4 of PT PLN (Persero) UPK to operatenormally. Keyword: DGA, Duval’s Triangle, fault gas, TDCG, transformer DAFTAR PUSTAKA[1] Demmassabu, A. R., L. S. Patras., dan F. Lisi. (2014). Analisa Kegagalan Transformator Daya Berdasarkan Hasil Uji DGA dengan Metode TDCG, Key Gas, Roger’s Ratio, Duval’s Triangle pada Gardu Induk. J. Teknik Elektro dan Komputer. 3(4) 1─10.[2] Faishal, M. A. R., Karnoto., dan T. Sukmadi. (2011). Analisis Indikasi Kegagalan Transformator dengan Metode Dissolved Gas Analysis. J. Transmisi. 3(13). 1─10.[3] IEC 60599. (2015). Mineral oilimpregnated electrical equipment in service: Guide to the interpretation of dissolved and free gases analysis. Geneva: IEC.[4] IEEE C57.104. (2019). International Standard – Guide for the Interpretation of Gases Generated in Mineral OilImmersed Transformers. IEEE - 2019. Piscataway: IEEE.[5] Kelman TRANSFIX Multiple Gas Transformer DGA. https://www.gegridsolutions.com/md/catalog/transfix.htm. (diakses 10 Oktober 2022).[6] Kementrian Energi dan Sumber Daya Mineral (ESDM). https://www.esdm.go.id/en/beritaunit/directorate-general-ofelectricity/kuartal-iii-2021-konsumsi-listrik-per-kapitameningkat-capai-1109-kwh. (diakses 12 September 2022).[7] Naibaho, N. (2017). Analisis Kegagalan Transformator Berdasarkan Hasil Pengujian DGA. J. SINERGI. 98─106.[8] PT. PLN (Persero), 2014. Buku Pedoman Pemeliharaan Transformator Daya. Jakarta: PT PLN (Persero).[9] PT. PLN (Persero). Singgle Line Diagram UIP3BS 2021. (diakses 15 Oktober 2022).[10] Yudhapraja, S., dan A.S. Prayogi. (2020). Analisa Gejala Kerusakan Transformator Berdasarkan Dissolved Gas AnalysisPembangkit PLTA Way Besai. J. NCIET. 1(1): 13─23.[11] Zope, N., Ali, S. I., Padnamaban, S., Bhaskar, M. S., dan Popa, L. M. (2018). Analysis of 132kV/33kV 15MVA Power TransformerDissolved Gas Using Transport-X Kelman Kit Through Duval’s Triangel and Roger’s Ratio Prediction. 2018 IEEE International Conference on Industrial Technology (ICIT). 1160-1164.